Airlines and the COVID-19 pandemic - McCarthy, Patrick S. (Advances in airline economics ;, 2024)
Billions of airline passengers, combined with conditions associated with airline travel and airports, create a conducive environment for the rapid spread of viruses. The COVID-19 pandemic impacted airlines, airports, and their operations significantly. Presently, the virus's threat to global public health, although a continuing concern, is significantly diminished and recovery is building. As nations' economies are returning to pre-pandemic environments, Airlines and the COVID-19 Pandemic assesses the pandemic's diverse impacts on the aviation sector, how airlines reacted to the pandemic, worked with governments, and adapted its operations and business models. This 11th Volume of the Advances in Airline Economics series provides new insights on the multidimensional impacts of the COVID-19 pandemic on the aviation sector in general and airlines in particular.